1981
DOI: 10.1002/ana.410090503
|View full text |Cite
|
Sign up to set email alerts
|

Methioninemia and myopathy: A new disorder

Abstract: A 7 1/2-year-old girl with hypermethioninemia, myopathy, and mental deficiency (IQ = 65) is described. The increased methionine was not associated with deficiency of methionine adenosyltransferase, which was normal or increased in liver, muscle, erythrocytes, and cultured fibroblasts. Methionyl-tRNA synthetase in fibroblasts was normal. The hypermethioninemia and a concurrently increased blood S-adenosylmethionine declined on a diet low in methionine. There was a diffuse, symmetrical, moderate proximal muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
6
10
0
Order By: Relevance
“…Primary generalized AdoHcy hydrolase deficiency seemed unlikely, and the authors concluded that the decreased hepatic AdoHcy activity might be secondary to liver disease. Gaull et al (31) described a girl with isolated hypermethioninemia and clinical findings and histopathology very similar to our patient: myopathy, retarded psychomotor development, mild hepatic dysfunction, and severely elevated creatine kinase. Hepatic MAT activity was not low, ruling out MAT IĶžIII deficiency.…”
Section: Previous Cases For Which Adohcy Hydrolase Deficiency Might Besupporting
confidence: 82%
“…Primary generalized AdoHcy hydrolase deficiency seemed unlikely, and the authors concluded that the decreased hepatic AdoHcy activity might be secondary to liver disease. Gaull et al (31) described a girl with isolated hypermethioninemia and clinical findings and histopathology very similar to our patient: myopathy, retarded psychomotor development, mild hepatic dysfunction, and severely elevated creatine kinase. Hepatic MAT activity was not low, ruling out MAT IĶžIII deficiency.…”
Section: Previous Cases For Which Adohcy Hydrolase Deficiency Might Besupporting
confidence: 82%
“…At the same time our patient was under investigation for similar findings and was also studied by Gaull and co-workers (Gaull et al 1979(Gaull et al , 1981. Extensive studies were done in both cases, but no primary enzyme deficiency was identified.…”
Section: Introductionsupporting
confidence: 63%
“…It seems highly likely the patient described in 1979, also from the former Yugoslavia (Gaull et al 1979(Gaull et al , 1981, had the same disorder (see further discussion below). There is no recognized connection of our patient's father to central/eastern Europe, but the known family history does not extend beyond three generations.…”
Section: Discussionmentioning
confidence: 92%
“…The girl, age years, described by Gaull and co-workers with elevation of plasma methionine, but not of tHcy, and above normal activity of liver methionine adenosyltransferase activity (Gaull et al 1981): This girl was similar to patients 1 and 2 in regard to having myopathy, muscle histology similar to theirs, and markedly elevated creatine kinase. As yet, it has not been possible to carry out further studies of this family.…”
Section: Possible Additional Cases Of Adohcy Deficiencysupporting
confidence: 52%
“…A male infant with unexplained hypermethioninaemia and myopathy, mentioned very briefly in the paper by Gaull and co-workers as a personal communication (1980) from Dr Neil Buist (Gaull et al 1981) Brain MRI changes in patient 2. (A) Brain MRI (axial T2) at age 26 days showing diffuse hyperintensity of white matter corresponding to unmyelinated axons.…”
Section: Possible Additional Cases Of Adohcy Deficiencymentioning
confidence: 99%